Meconium aspiration pneumonia in Murrah buffalo calves - Kamdi, Bhupesh; Singh, Rajendra; Singh, Vidya; Singh, Shailendra; Kumar, Pawan (Buffalo Bulletin, 2023)
Meconium aspiration syndrome (MAS) is caused due to respiratory distress to the fetus during or before parturition. As a result of asphyxia, the fetal gasping causes meconic amniotic fluid entry into the respiratory air passages and pulmonary complications, and sometimes death of the newborn. In the present study, two cases of MAS in Murrah buffalo calves born full term by assisted delivery and died after few hours of delivery were received for routine postmortem examination. Necropsy examination revealed diffuse mosaic-pattern - like lesions in the lungs characterized by dark brown-to-red deflated (atelectatic) lobes and small irregular pale raised multi focal partially inflated tiny areas amidst the atelectatic lobes. The respiratory passages were filled with aspirated substances. Microscopically, bronchoalveloar lumen contained with keratin, squames and subtle meconium along with mild infiltration of neutrophils in the alveolar parenchyma. The MAS in Murrah buffalo calves in the present study was similar in presentation with that reported in human babies due to the MAS. These cases add further information on MAS in the buffaloes to the scanty literature on this condition.